THE ROLE OF THE LANGUAGE SECTION IN IMPROVING THE ARABIC AND ENGLISH SPEAKING SKILLS OF THE STUDENTS OF THE HUBULO ISLAMIC BOARDING SCHOOL - Mariaty Podungge; Alvons Habibie (Universitas Labuhanbatu, 2022)
This study aims to determine the role of the language department in improving the Arabic and English speaking skills of students at the Hubulo Islamic Boarding School. The research method used is a qualitative research method. Data was collected through observation, interviews and documentation. The results showed that (1) The role of the language section can be seen in their responsibilities when carrying out daily activities, weekly activities, monthly activities and annual activities 2) There are several supporting and inhibiting factors in the implementation of activities. On the supporting factor, namely the existence of cooperation between the language sections in carrying out their respective tasks, supporting facilities and a conducive pesantren environment ; on the inhibiting factors, namely the lack of members of the language section, there is no special coach who guides the ability to speak Arabic and English Â and the lack of awareness of students in obeying the rules using Arabic and EnglishÂ Key Word; Role, Language section, Speak, Hubulo Â